Analysis on Grammatical Error of Student’s Writing Descriptive Text - Sri Rahayu, Yayu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
The research paper is entitled “Analysis on GraError of Student’s Writing Descriptive Text”. The aims of the research were to find out what kinds of grammatical error made by eight grade students of SMP Negeri 1 Pasirjambu in writing descriptive text and to analyze what causes of the grammatical error in writing descriptive text. The sample of the data was collected by giving writing test , which consisted of 31 students. Qualitative research was used by the researcher as the research method. From the total of 246 sentences of the samples, the research finding showed that misformation was the highest error that students made in writing descriptive text. The percentage of the errors was 104 (53%) from the total error 196. Whereas, the lowest percentage of the error was found in misordering with the percentage 19 (10%). On the other hand, there were some causes of the error made by students of the eight grade of Junior High School in writing descriptive text suc as the language interference, carelessness and translation. The highest cause of error on percentage 53% was found in first language interference. Meanwhile, the lowest cause of error was translation with the total percentage 10 %. It showed that the students still had difficulties in writing descriptive text. It was caused by the language interference, the second was Therefore, the teacher had to give the appropriate method for the students in teaching descriptive text and using appripiate media and interesting material to help them easy to understand the lesson. So that the error related to writing descriptive text could be minimized. Key words: Descriptive text, error, error analysis, grammar